EFFECT OF MANAGERIAL ABILITY, MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN A MULTINATIONAL ORGANIZATION - Nia Kurnia; Deviari Damalita (PT. Berkah Digital Teknologi, 2022)
This study uses a quantitative approach to see the causal relationship of several factors that influence employee performance. The population in this study were the employees of the Dinas Pendidikan dan Kebudayaan Kabupaten Kuningan Regency totaling 61 employees. Data were collected by questionnaire and document study, after which the data were tested for validity and reliability. The results showed that Managerial Ability, Motivation and Work Discipline had an effect on employee performance simultaneously. The Multiple Determination Coefficient in this study uses the adjusted R square value because the independent variables in this study are more than 2 in estimating the influence of the two independent variables studied. From the adjusted R Square value data of 0.583, Although the influence of the independent variable on the dependent variable is included in the medium classification. According to the author's suggestion, it should be further improved, especially in terms of managerial ability from the leadership, then the motivation that must be increased and no less important is Work Discipline from the employees themselves, so this will have an impact on increasing employee performance.